TRANSPORTASI BENIH IKAN NILA (OREOCHROMIS NILOTICUS) DENGAN MENGGUNAKAN EKSTRAK BUNGA KAMBOJA (PLUMERIA ACUMINATA) SEBAGAI ANESTESI - S Pellu; Felix Rebhung (Jurnal Akuatik, 2018)
Abstract - The study to know the anesthesia effect of frangipani flower extract on tilapia jureniles (Oreochromis niloticus) during transportation has been done at the Laboratory ofthe Faculty of Marine and Fisheries Nusa Cendana university. the animals were managet in containers and arranged based on complete randomized design (t3,t3) with treatment A (7,584 mg / L frangipani flower extract), B (9,304 mg / L frangipani flower extract), Control (without frangipani flower extract). The parameters observed were fainting time, long recovered consciousness, survival rate and water quality (temperature, pH, DO). The results showed that the effect of frangipani flower extract were significant as observed on period of fainting, long recovered conscious and survival rate. The concentration of frangipani flower extract had no significant effect on survival rate. The most effective concentration of frangipani flower extract for anesthetic of tilapia jureniles transport was 7.5 84 mg / L. Keywords : Extract, Frangipani Flower, Transportation Of Seed, Indigo, Anesthesia